Geopolitical interests of modern Georgia - Vakulovych, Uliana (Lesya Ukrainka Volyn National University, 2024)
The first section of the bachelor's thesis summarizes the essence of the concept of geopolitics and geopolitical interest. It is established that geopolitics studies the relationship between geography, power and politics. It analyzes how geographical factors, such as location, resources, and topography, influence the behavior of states and their interactions on the world stage. This study examines the theoretical and methodological foundations of the study of the geopolitical interests of states, with a special emphasis on Georgia. Further research provides an overview of the current state of research on this topic in the current scientific literature, identifying gaps and areas for further research. It also discusses the methodological aspects of conducting research on the geopolitical interests of states. In the second chapter of the bachelor's work, were investigated the main factors that influenced the formation of geopolitical interests of modern Georgia. The study examines historical, political, legal and socio-economic factors, providing an idea of the prerequisites and ways of conducting its foreign policy. The third bachelor's degree program analyses the specifics of the implementation of Georgia's geopolitic interests in the current region, presents the characteristics of Georgia's current geopolitic strategy, the main vectors, the role of the country's regions, such as Ukraine, and the problems of the prospects that Georgia faces in its own strategic goals. Based on the results of the work, conclusions are drawn. Geopolitical interests are those national interests that describe the strategic or political goals of a particular country, and are directly related to the geopolitical location of the state, resources, influence and security. This may include diplomatic alliances, control of territories, economic relations, and other factors that affect its position in the world. The historical development of Georgia's geopolitical interests can be divided into two periods: before gaining independence, and the period after Georgia gained independence. The characteristic features of the geopolitical interests of modern Georgia are: a dynamic desire for security, prosperity and integration into the wider international community, cooperation with the EU and NATO countries, the fight against terrorism and the resolution of conflicts and the territory of the state. The main problems in the implementation of Georgia's geopolitical interests are unresolved regional conflicts, external influences and constraints on economic development. The presence of conflicts in Abkhazia and South Ossetia, which undermine the sovereignty and stability of Georgia, external influence, in particular from Russia, threatens its Euro-Atlantic aspirations and territorial integrity. However, despite these challenges, the prospects for Georgia's geopolitical interests lie in diplomatic initiatives to resolve conflicts, diversify international partnerships, and continue economic reforms to increase competitiveness and integrate into world markets. Promising and strategically important in Georgia's geopolitical strategy are relations with the EU, NATO, Ukraine, the countries of the Middle East and Central Asia.
Keywords: Georgia; geopolitical interests; state; factors; development; political prerequisites; socio-economic factors; security